How words make the world: language materialities and the circulation of the Sakha algys - Ferguson, Jenanne (My University, 2021)
This article investigates contemporary uses of the Sakha language algys (blessing poems) and reveals the “old” and “new” types of language materiality present in this genre of ritual poetry. Focusing primarily on one example of algys shared online in 2018, I discuss how performing algys has always involved close interconnection between language and the material world and present the changing contexts and forms of algys transmission that highlight both fixity and fluidity in the way speakers conceive of language and materiality. Despite the new mobilities and technologies that build upon the previously established written textual forms of this poetry—and contribute to its continued circulation and transmission—certain elements of traditional algys remains salient for speakers, reinforced by ideologies or ontologies of language that foreground the power of the (spoken) word. This is connected to the production of qualia and the invocation of chronotopes. Thus, while textual forms further enable processes of citationality as they are circulated online; the written words alone do not constitute an algys. Rather, here the importance of embodied, spoken language materiality is at the fore.
Keywords: language materiality; language revitalization; ontologies of language; ritual poetry; Sakha language; verbal art